2012
DOI: 10.1007/s00284-012-0215-3
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of ABC Efflux Pump, Rv1217c–Rv1218c, and Its Association with Multidrug Resistance of Mycobacterium tuberculosis in China

Abstract: Currently the treatment of Mycobacterium tuberculosis (TB) infection is largely limited due to the prevalence of multidrug resistance strains. Over-expressing the efflux pumps such as the ATP-binding cassette (ABC) transporter has been reported to significantly contribute to its resistance to several antibiotics. This study investigated the expression profile of one important ABC efflux pump, Rv1217c-Rv1218c, by quantitative real-time PCR (RT-qPCR) in clinical isolates from China, which also revealed its assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 20 publications
1
45
0
2
Order By: Relevance
“…A low frequency of mutation in eth A gene of ethambutol resistant isolates have also been reported earlier and may suggest existence of some other mechanisms such as efflux pump for ethionamide resistance [56,67]. …”
Section: Discussionmentioning
confidence: 57%
“…A low frequency of mutation in eth A gene of ethambutol resistant isolates have also been reported earlier and may suggest existence of some other mechanisms such as efflux pump for ethionamide resistance [56,67]. …”
Section: Discussionmentioning
confidence: 57%
“…It has been observed that the expression level of the Rv1217c-Rv1218c multidrug efflux pump is significantly increased in clinically isolated MDR-TB strains in comparison with that of the wild-type H37Rv M. tuberculosis. 32 In this article, we have reported the crystal structure of the Rv1219c regulator, which controls the expression level of Rv1217c-Rv1218c. The available of this crystal structure may allow us to rationally design agents that block the function of this regulator and diminish the expression of the multidrug efflux pump, which in turn heightens the sensitivity of this pathogen to antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Each subunit of Rv1219c is composed of 10 helices (a1-a10 and a1 0 -a10 0 , respectively). The helices of Rv1219c are designated numerically from the N-terminus as a1 (7-23), a2 (29)(30)(31)(32)(33)(34)(35)(36), a3 (40-47), a4 (50-74), a5 (78-86), a6 (92-104), a7 (108-130), a8 (139-160), a9 (166-188), and a10 (194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206). In this arrangement, the smaller N-terminal domain includes helices a1 through a3 and the N-terminal end of a4 (residues 50-60), with a2 and a3 forming a typical helix-turn-helix motif.…”
Section: Overall Structure Of Rv1219cmentioning
confidence: 99%
“…In clinical strains of MTB, increased expression of efflux pumps occurs mainly as a result of induction in response to antibiotic stress (Jiang et al, 2008; Gupta et al, 2010a; Li et al, 2015). For instance, studies that investigated the relevance of active efflux in the drug resistance of clinical strains of MTB indicated that jefA, drrA, drrB, efpA, mmr , and RV1217-Rv1218 efflux pumps were overexpressed under INH and RIF stress (Wang et al, 2013; Blair et al, 2015; Li et al, 2015). Furthermore, several studies indicated that some RIF or INH-resistant strains of MTB did not have sequence alterations in the core region of the drug target encoding genes (e.g., rpoB, katG, inhA ; Yamchi et al, 2015; Manson et al, 2017).…”
Section: Drug Resistance Mechanisms In Mycobacteriamentioning
confidence: 99%